4(3-4t)=6(3-3t)

Simple and best practice solution for 4(3-4t)=6(3-3t) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(3-4t)=6(3-3t) equation:


Simplifying
4(3 + -4t) = 6(3 + -3t)
(3 * 4 + -4t * 4) = 6(3 + -3t)
(12 + -16t) = 6(3 + -3t)
12 + -16t = (3 * 6 + -3t * 6)
12 + -16t = (18 + -18t)

Solving
12 + -16t = 18 + -18t

Solving for variable 't'.

Move all terms containing t to the left, all other terms to the right.

Add '18t' to each side of the equation.
12 + -16t + 18t = 18 + -18t + 18t

Combine like terms: -16t + 18t = 2t
12 + 2t = 18 + -18t + 18t

Combine like terms: -18t + 18t = 0
12 + 2t = 18 + 0
12 + 2t = 18

Add '-12' to each side of the equation.
12 + -12 + 2t = 18 + -12

Combine like terms: 12 + -12 = 0
0 + 2t = 18 + -12
2t = 18 + -12

Combine like terms: 18 + -12 = 6
2t = 6

Divide each side by '2'.
t = 3

Simplifying
t = 3

See similar equations:

| 3-2x=3(x-4) | | 4v-8=8(v+4) | | 5(2k-3)=15k-25 | | 6(2n-5)=42 | | -3z-15=2z+3 | | -2(v-1)=-4v-10 | | 3x+6=4x-1 | | -(3y+5)-(-2y-7)=-3 | | -4w-14=3(w+7) | | 5k-14=3k-12 | | 7r-5(1+r)=5 | | 5(2p+4)=10 | | 11=-7y+4 | | 4n-6=2n+6 | | 7n-5n+7=-11 | | 6x+9=27 | | 5x+6=51 | | -7.6x=15.2 | | 8t=-76 | | 8r=-24 | | 6(3b+1)+(19b-6)=0 | | x=-1.076923077+0.5128205128X | | 8x+40=56 | | 7x+32=60 | | 7x+20=90 | | x(5x+11)=12 | | 8x+26=2 | | 2.2=-4u+27.8 | | 8x+23=63 | | 4(3m+6)=2(6m+8) | | 2x+22=-10 | | 4(3m+6)=(6m+8) |

Equations solver categories